Children and youth with asperger syndrome - Smith Myles, Brenda (United States of America : Corwin Press, 2005)
Written to be inmediately accessible to busy educators and others coming in contact with students with Asperger Syndrome.
Contents Introduction: Characteristics of children and youth with Asperger Syndrome 1. Adaptations for success in General Education Settings 2. Environmental modification 3. Academic modifications 4. Emotional and Bechavioral supports
Contiene referencias bibliográficas
Keywords: ASPERGER SYNDROME; SINDROME DE ASPERGER